Spectroscopic Identification and Chemical Distribution of HII Regions in the Galactic Anti-center Area from LAMOST. (19th September 2018) - Wang, Li-Li; Luo, A-Li; Hou, Wen; Wang, Meng-Xin; Du, Bing; Qin, Li; Han, Jin-Shu
Abstract: We spectroscopically identify 101 Galactic HII regions using spectra from the Large Sky Area Multi-Object Fiber Spectroscopic Telescope (LAMOST) survey, cross-matched with an HII region catalog derived from the all-sky Wide-Field Infrared Survey Explorer ( WISE ) data. Among all HII regions in our sample, 47 sources are newly confirmed. Spatially, most of our identified HII regions are located in the anti-center area of the Galaxy. For each of the HII regions, we accurately extract and measure the nebular emission lines of the spectra, and estimate the oxygen abundances using the strong-line method. We focus on the abundance distribution of HII regions in the Galactic anti-center area. Accordingly, we derive the oxygen abundance gradient with a slope of −0.036 ± 0.004 dex kpc −1, covering a range of R G from 8.1 to 19.3 kpc. In particular, we also fit the outer disk objects with a slope of −0.039 ± 0.012 dex kpc −1, which indicates that there is no flattening of the radial oxygen gradient in the outer Galactic disk.